2016
DOI: 10.1016/j.jped.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management and postoperative prognosis of newborns submitted to primary surgical repair of gastroschisis

Abstract: Early start of enteral feeding and small, gradual increase of volume can shorten the use of parenteral nutrition. This management strategy contributes to reduce the incidence of infection and length of hospital stay of newborns with gastroschisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
1
11
0
3
Order By: Relevance
“…Full enteral feeding at a median of 18 days on the GS guideline is consistent with the current literature for feeding advancement in infants with simple gastroschisis. 27 Although the infants managed on the 1-day feeding guideline reached FEN in a shorter period of time (11 days), we contend that this difference is minimally clinically Consistent with previous studies, we found that although increasing the rate of feeding advancement can result in a shorter time to FEN in infants with gastroschisis, this speed brings with it a risk of NEC. 28 We designed our GS guideline to limit this risk by advancing feeding every other day for the first half of the feeding advancement process.…”
Section: Discussionsupporting
confidence: 89%
“…Full enteral feeding at a median of 18 days on the GS guideline is consistent with the current literature for feeding advancement in infants with simple gastroschisis. 27 Although the infants managed on the 1-day feeding guideline reached FEN in a shorter period of time (11 days), we contend that this difference is minimally clinically Consistent with previous studies, we found that although increasing the rate of feeding advancement can result in a shorter time to FEN in infants with gastroschisis, this speed brings with it a risk of NEC. 28 We designed our GS guideline to limit this risk by advancing feeding every other day for the first half of the feeding advancement process.…”
Section: Discussionsupporting
confidence: 89%
“…Gastroschisis occurs in 5 of 10,000 live births with a survival of greater than 90% however, there is often significant associated morbidity [3, 4]. Difficulties in commencing and progressing enteral feeds [5, 6], is well recognized in this group and this difficulty is thought to be due to the poor gut motility as a result of the bowel exposure and thickening. The delay in the establishment of enteral feeds often contributes to lengthy requirements for central venous access, dependence on total parenteral nutrition (TPN), small bowel bacterial overgrowth (SBBO), increased risk of sepsis and TPN related cholestasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study conducted in the state of Minas Gerais, southeastern Brazil, found higher mortality rates (14.7%) compared to developing countries 11 , with deaths usually occurring among neonates with intestinal impairment or sepsis 7 . With regard to treatment of the NB with gastroschisis in the immediate postpartum period, a silo, i.e., a polyvinyl chloride (PVC) bag, helps prevent heat and fluid loss and allows for intestinal loops to be returned to the abdominal cavity until the surgical closure of the abdominal wall 7 .…”
mentioning
confidence: 96%
“…Primary closure consists of abdominal fascial closure after reduction of eviscerated loops, and staggered (or secondary) closure uses a silo to hold the exposed loops and reduce them gradually after surgery, resulting in the correction of the defect or including surgical reinterventions 5 to 10 days after primary closure 7 . The most common postoperative complications consist of necrotizing enterocolitis, short bowel syndrome, malabsorption, intestinal obstruction, and cholestasis, due to prolonged use of parenteral nutrition 9,10 , but neonate dietary tolerance is increased when diet is gradually started with smaller volumes 11 . The relevance of the present study lies on the importance of gastroschisis as an abdominal wall malformation considered as a rare event with a multifactorial etiology 12 .…”
mentioning
confidence: 99%
See 1 more Smart Citation